Identification of ex-ante and ex-post transaction costs in industrial construction engineering projects - Fonseca, Fábio Bellotti da; Vanalle, Rosangela Maria; Camarotto, João Alberto (Journal of Civil Engineering and Management, 2018)
Construction costs comprise not only production but also transaction costs, which can be categorized as ex-ante (pre-contractual) and ex-post (post-contractual) costs. No evidence has been found in the literature of research about transaction costs in industrial construction engineering projects. The objective of this paper is to identify ex-ante and ex-post transaction costs in industrial engineering construction projects. To accomplish this, empirical research with 4 case studies was conducted with a large engineering firm in Brazil. This research not only identified transaction costs already found by others, dividing them into ex-ante and ex-post, but also identified that travel, RFP clarification, support to strategic decisions of the owner and knowledge transfer are transaction costs not previously identified in the researched literature but that are very relevant to the respective subject. Therefore, this research confirms that transaction costs should be considered ex-ante and ex-post by owners and contractors in industrial construction engineering projects and enlightens academics and practitioners on ways to achieve the reduction of such costs.